"New" cyanobacterial blooms are not new: two centuries of lake production are related to ice cover and land use. Issue 6 (17th June 2020) - Ewing, Holly A.; Weathers, Kathleen C.; Cottingham, Kathryn L.; Leavitt, Peter R.; Greer, Meredith L.; Carey, Cayelan C.; Steele, Bethel G.; Fiorillo, Alyeska U.; Sowles, John P.
Abstract: Recent cyanobacterial blooms in otherwise unproductive lakes may be warning signs of impending eutrophication in lakes important for recreation and drinking water, but little is known of their historical precedence or mechanisms of regulation. Here, we examined long‐term sedimentary records of both general and taxon‐specific trophic proxies from seven lakes of varying productivity in the northeastern United States to investigate their relationship to historical in‐lake, watershed, and climatic drivers of trophic status. Analysis of fossil pigments (carotenoids and chlorophylls) revealed variable patterns of past primary production across lakes over two centuries despite broadly similar changes in regional climate and land use. Sediment abundance of the cyanobacterium Gloeotrichia, a large, toxic, nitrogen‐fixing taxon common in recent blooms in this region, revealed that this was not a new taxon in the phytoplankton communities but rather had been present for centuries. Histories of Gloeotrichia abundance differed strikingly across lakes and were not consistently associated with most other sediment proxies of trophic status. Changes in ice cover most often coincided with changes in fossil pigments, and changes in watershed land use were often related to changes in Gloeotrichia abundance, although no single climatic or land‐use factor was associated with proxy changes across all seven lakes. The degree to which changes in lake sediment records co‐occurred with changes in the timing of ice‐out or agricultural land use was negatively correlated with the ratio of watershed area to lake area. Thus, both climate and land management appeared to play key roles in regulation of primary production in these lakes, although the manner in which these factors influenced lakes was mediated by catchment morphometry. Improved understanding of the past interactions between climate change, land use, landscape setting, and water quality underscores the complexity of mechanisms regulating lake and cyanobacterial production and highlights the necessity of considering these interactions—rather than searching for a singular mechanism—when evaluating the causes of ongoing changes in low‐nutrient lakes.